REWARD AND PUNISHMENT STRATEGIES OF ISLAMIC RELIGION TEACHERS IN IMPROVING STUDENT DISCIPLINE - Qudriyah, Faizatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to identify reward and punishment strategies for student discipline at Mohammad Shodiq Middle School. Researchers used a qualitative descriptive approach using observation and interview methods. The location of this research was at Mohammad Shodiq Maron Middle School, Probolinggo. At Muhammad Shodiq Middle School, several disciplinary problems were found by students at school, such as not coming to school on time. So a strategy is needed by the teacher to make students more disciplined, one of which is through reward and punishment strategies. The results of the research state that the reward and punishment methods used by teachers are to motivate students to obey and comply with the rules set by the school with the aim of establishing student discipline. Using this reward and punishment strategy is able to provide motivation to Mohammad Shodiq Middle School students towards obeying and complying with existing regulations at school so that students become more disciplined at school.